Studies on the fat mass and obesity-associated (FTO) gene and its impact on obesity-associated diseases - Chaoqun Huang; Wei Chen; Xinxia Wang (Genes and Diseases, 2023)
Obesity has become a major health crisis in the past ∼50 years. The fat mass and obesity-associated (FTO) gene, identified by genome-wide association studies (GWAS), was first reported to be positively associated with obesity in humans. Mice with more copies of the FTO gene were observed to be obese, while loss of the gene in mice was found to protect from obesity. Later, FTO was found to encode an m6A RNA demethylase and has a profound effect on many biological and metabolic processes. In this review, we first summarize recent studies that demonstrate the critical roles and regulatory mechanisms of FTO in obesity and metabolic disease. Second, we discuss the ongoing debates concerning the association between FTO polymorphisms and obesity. Third, since several small molecule drugs and micronutrients have been found to regulate metabolic homeostasis through controlling the expression or activity of FTO, we highlight the broad potential of targeting FTO for obesity treatment. Improving our understanding of FTO and the underlying mechanisms may provide new approaches for treating obesity and metabolic diseases.